Neutron spectroscopy with N2-filled high-pressure large-volume spherical proportional counters. Issue 1 (1st November 2022) - Giomataris, I; Green, S; Katsioulas, I.; Knights, P; Manthos, I; Matthews, J; Neep, T; Nikolopoulos, K; Papaevangelou, T; Phoenix, B; Sanders, J; Ward, R
Abstract : Precise in-situ measurements of the neutron flux in underground laboratories is crucial for direct dark matter searches, as neutron induced backgrounds can mimic the typical dark matter signal. The development of a novel neutron spectroscopy technique using Spherical Proportional Counters is investigated. The detector is operated with nitrogen and is sensitive to both fast and thermal neutrons through the 14 N(n, α ) 11 B and 14 N(n, p) 14 C reactions. This method holds potential to be a safe, inexpensive, effective, and reliable alternative to 3 He-based detectors. Measurements of fast and thermal neutrons from an Am-Be source with a Spherical Proportional Counter operated at pressures up to 2 bar at Birmingham are discussed.